Assessing the association between diet quality and sociodemographic factors in young Saudi adults - Alzaben, Abeer Salman; Alresheedi, Kholoud Rashed; Bakry, Huny M.; Ozayb, Rahaf Abdullah; Aldawsari, Halah Abdulaziz; Alnamshan, Arwa Obaid; Bawazeer, Nahla M. (Frontiers in Nutrition, 2025)
ObjectiveThis study aimed to evaluate diet quality (DQ) using the Short Healthy Eating Index (sHEI) and explore the relationship between DQ and sociodemographic factors among young adults in Saudi Arabia.MethodsThis observational cross-sectional study was conducted in Saudi Arabia among young adults aged 18–25 years, through a questionnaire distributed online using social media. The participants provided consent and demographic information, and DQ was assessed using a validated sHEI questionnaire. The questionnaire was translated to Arabic and adapted for local relevance Data analyses were performed. Statistical significance was defined as p ≤ 0.05.ResultsA total of 605 participants (average age 20.8 ± 2.0 years old) were recruited. More than half of the participants had a normal body mass index. The average total sHEI score, adequacy, and moderation scores were 44.98 ± 9.36, 29.56 ± 7.16, and 15.40 ± 5.71, respectively. BMI was negatively associated (weak association) with the adequacy score (p < 0.05). There were significant associations between the adequacy score, total sHEI score, sex, and region (p < 0.05). Being female was associated with good adequacy scores (p = 0.010). Being female (p = 0.001) and residing in the southern region area (p = 0.028) were associated with good total sHEI scores (p = 0.005).ConclusionMost individuals had a low sHEI, indicating poor DQ. Nutrition education should focus on DQ, sustainable nutrition, and eating behaviors. Future studies should assess the association between DQ and sociodemographic factors such as gender region and other lifestyle factors such as physical activity, sleep pattern, and smoking.